2011
DOI: 10.1364/ol.36.000169
|View full text |Cite
|
Sign up to set email alerts
|

Eye-safe 2μm luminescence from thulium-doped silicon

Abstract: We report on photoluminescence in the 1:7-2:1 μm range of silicon doped with thulium. This is achieved by the implantation of Tm into silicon that has been codoped with boron to reduce the thermal quenching. At least six strong lines can be distinguished at 80 K; at 300 K, the spectrum is dominated by the main emission at 2 μm. These emissions are attributed to the trivalent Tm 3þ internal transitions between the first excited state and the ground state. © 2011 Optical Society of America OCIS codes: 250.5230,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The incorporation of Tm leads to emission of light over two important wavelength regions, 1.2-1.4 lm and 1.7-2.1 lm, which can both support lasing and indeed form the basis of commercially available, optically pumped lasers. In addition, the electrical excitation of the Tm emission has been demonstrated in silicon light emitting diodes under ordinary forward bias 4 and, most recently, 5 room temperature luminescence has been reported at the important, eye-safe, 2 lm wavelength. Significantly, efficient Tm emission in silicon is only achieved in samples coimplanted with B, when dislocation loops are introduced.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of Tm leads to emission of light over two important wavelength regions, 1.2-1.4 lm and 1.7-2.1 lm, which can both support lasing and indeed form the basis of commercially available, optically pumped lasers. In addition, the electrical excitation of the Tm emission has been demonstrated in silicon light emitting diodes under ordinary forward bias 4 and, most recently, 5 room temperature luminescence has been reported at the important, eye-safe, 2 lm wavelength. Significantly, efficient Tm emission in silicon is only achieved in samples coimplanted with B, when dislocation loops are introduced.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] PL and EL from silicon and III-V semiconductors incorporating the RE thulium have also been achieved-transitions between the Tm 3+ lowest excited states and the ground state lead to emissions around 0.8, 1.2, and 2 µm. [22][23][24] Both Er and Tm in silicon, and indeed all others RE reported in silicon Silicon-Modifi ed Rare-Earth Transitions-A New Route to Near-and Mid-IR Photonics Manon A. Lourenço , * Mark A. Hughes , Khue T. Lai , Imran M. Sofi , Willy Ludurczak , Lewis Wong , Russell M. Gwilliam , and Kevin P. Homewood Silicon underpins microelectronics but lacks the photonic capability needed for next-generation systems and currently relies on a highly undesirable hybridization of separate discrete devices using direct band gap semiconductors. Rare-earth (RE) implantation is a promising approach to bestow photonic capability to silicon but is limited to internal RE transition wavelengths.…”
mentioning
confidence: 99%
“…The dislocation loops form a barrier for carrier diffusion, thus reducing competing nonradiative recombination. This has led to efficient luminescence [photoluminescence (PL) and electroluminescence] at 1.1 μm from undoped silicon devices [8], at 1.5 μm from Er-doped structures [9], and at 1.3 and 2 μm from Tm-doped [5][6][7] structures.The RE Dy as an emissive optical center has the potential to be utilized in technologically important optoelectronics and medical applications due to its spectral range emission that extends from the UV to the near infrared. …”
mentioning
confidence: 99%
“…Luminescence from other RE ions in III-V materials has also been achieved, and an Eu-doped GaN visible laser has been demonstrated [3]. In contrast to III-V materials, light emission from RE-doped crystalline silicon has been restricted to Er [2] and, more recently, Tm [4][5][6][7]. Early reports [2] on the Er:Si system indicated that the solubility of Er in silicon is low, making the incorporation of high concentrations of erbium difficult and leading to very poor luminescence at room temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation